(untitled) (The Peerian Journal, 2025)
This article provides a comprehensive legal and sociological analysis of the key drivers behind persistent corruption in Uzbekistan. It identifies three primary causes: (1) inadequate salaries among public officials, which encourage bribery and embezzlement; (2) the lack of transparency in government recruitment and regulatory practices, which enables nepotism and abuse of power; and (3) the cultural normalization of corruption across various sectors, including education and healthcare. Drawing from legal texts, empirical data, and recent policy initiatives such as the use of police body cameras and anti-corruption education programs, the article explores the systemic nature of corruption and proposes institutional reforms. These include increased publication of regulatory documents, mandatory transparency in recruitment, and anti-corruption education in schools. By addressing both legal loopholes and deep-seated cultural practices, the proposed solutions aim to promote accountability, deter malpractice, and instill ethical governance practices in Uzbekistan.